Bioorthogonal Reactions in Activity-Based Protein Profiling - Verhelst, Steven H. L. (Molecules, 2020)
Activity-based protein profiling (ABPP) is a powerful technique to label and detect active enzyme species within cell lysates, cells, or whole animals. In the last two decades, a wide variety of applications and experimental read-out techniques have been pursued in order to increase our understanding of physiological and pathological processes, to identify novel drug targets, to evaluate selectivity of drugs, and to image probe targets in cells. Bioorthogonal chemistry has substantially contributed to the field of ABPP, as it allows the introduction of tags, which may be bulky or have unfavorable physicochemical properties, at a late stage in the experiment. In this review, we give an overview of the bioorthogonal reactions that have been implemented in ABPP, provide examples of applications of bioorthogonal chemistry in ABPP, and share some thoughts on future directions.